Level of Public Satisfaction with the Services of the Mataram City Regional Financial Agency in 2021 - Ida Wayan Demung (International Journal of Organizational Behavior and Policy, 2023)
The Regional Financial Board of the City of Mataram carries out its duties to serve the public interest directly or indirectly, including in the internal section and even covering several aspects, especially the taxpayer. The results of the assessment carried out become very important evaluation material in improving the quality of excellent and synergized services. The existing strengths in the strategy are expected to encourage increased employee performance to realize outcomes that are able to provide satisfaction to all stakeholders. The method used in this community satisfaction survey uses a quantitative approach. Data collection used a closed questionnaire with a Likert scale measurement. The results of the analysis of the community satisfaction index assessment at the Regional Finance Board include a sample of 477 respondents with an IKM score in 2021 of 77.90. The IKM Conversion Interval Value is 77.95, even from the Values: perception, interval, Conversion interval, service quality, and Service Unit Performance states that the performance of the Mataram City Regional Financial Agency in 2021 is in the "Good" category. can continuously improve and provide quality services and of course, be able to satisfy in various aspects.